From Genome to Phenotype: An Integrative Approach to Evaluate the Biodiversity of Lactococcus lactis - Laroute, Valérie (Microorganisms, 2017)
Lactococcus lactis is one of the most extensively used lactic acid bacteria for the manufacture of dairy products. Exploring the biodiversity of L. lactis is extremely promising both to acquire new knowledge and for food and health-driven applications. L. lactis is divided into four subspecies: lactis, cremoris, hordniae and tructae, but only subsp. lactis and subsp. cremoris are of industrial interest. Due to its various biotopes, Lactococcus subsp. lactis is considered the most diverse. The diversity of L. lactis subsp. lactis has been assessed at genetic, genomic and phenotypic levels. Multi-Locus Sequence Type (MLST) analysis of strains from different origins revealed that the subsp. lactis can be classified in two groups: “domesticated” strains with low genetic diversity, and “environmental” strains that are the main contributors of the genetic diversity of the subsp. lactis. As expected, the phenotype investigation of L. lactis strains reported here revealed highly diverse carbohydrate metabolism, especially in plant- and gut-derived carbohydrates, diacetyl production and stress survival. The integration of genotypic and phenotypic studies could improve the relevance of screening culture collections for the selection of strains dedicated to specific functions and applications.